Drosophilidae (Insecta, Diptera) in the state of Pará (Brazil) - Santa-Brígida, Rosângela; Schmitz, Hermes José; Martins, Marlúcia Bonifácio (Biota Neotropica, 2017)
Abstract This list contains information on the Drosophilidae that occur in the Brazilian state of Pará, Amazon biome, and an analysis of the current knowledge of Drosophilidae based on museum material and literature records. This list includes a detailed account of the material deposited in the entomological collections of the Museu Paraense Emílio Goeldi and Museu de Zoologia da Universidade de São Paulo, up to 2015. In total, 122 species of Drosophilidae were registered, including 27 new records for the state of Pará and 22 are new records for the Amazon; for instance, the genera Diathoneura and Rhinoleucophenga, and three new records for Brazil, (Drosophila fasciola, Diathoneura flavolineata and Drosophila neochracea). The state of Pará is the third state in Brazil in terms of numbers of species of Drosophilidae, with 17% locally native species. Despite the high species richness, there is still a lot to be known about the states's Drosophilidae fauna. This study highlights the importance of scientific collections, particularly as an aid to study regional biodiversity.